(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2023)
In an environment marked by unpredictability and uncertainty, the strategy for fostering investment activity becomes a complex and dynamic endeavor. This abstract explores the essential components of a strategy for developing investment activity in uncertain conditions. It delves into risk management, diversification, market analysis, and adaptability as key elements of such a strategy. Additionally, it emphasizes the importance of flexibility and agility in decision-making to successfully navigate the ever-changing landscape of investment opportunities.